MATHEMATICAL MODELING OF THE PROCESSES OF NONLINEAR DEFORMATION OF CONSTRUCTIVE THERMO-MAGNETIC-ELASTIC PLATES (American Journal of Technology and Applied Sciences, 2024)
The article is devoted to the development of a mathematical model of the process of geometric nonlinear deformation of thin thermo-magnetic-elastic plates of a complex structural shape based on the Hamilton-Ostrogradsky variational principle and conducting calculation experiments. To solve the equation, a calculation algorithm was developed using R-function, Bubnov-Galerkin, Newmark, Gaussian, Gaussian squares, and Iteration number methods. Calculation experiments were carried out in various mechanical states of the magneto-elastic plate, its borders were tightly fixed, one side was hinged and the other side was free, and numerical results were obtained. A comparative analysis of the results of the calculations was presented.